2009
DOI: 10.1073/pnas.0811965106
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of human Rad51 nucleoprotein dynamics on individual DNA molecules

Abstract: Rad51 protein (Rad51) is central to recombinational repair of double-strand DNA breaks. It polymerizes onto DNA and promotes strand exchange between homologous chromosomes. We visualized the real-time assembly and disassembly of human Rad51 nucleoprotein filaments on double-stranded DNA by single-molecule fluorescence microscopy. Rad51 assembly extends the DNA by Ϸ65%. Nucleoprotein filament formation occurs via rapid nucleation followed by growth from these nuclei. Growth does not continue indefinitely, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
161
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(191 citation statements)
references
References 47 publications
28
161
0
Order By: Relevance
“…We observed that the polymerization of hRad51 on dsDNA requires a minimal concentration of approximately 100 nM to initiate. This is consistent with previous results independently obtained both with conventional MT (20) and in single-molecule videomicroscopy (21) confirming the existence of a threshold concentration for hRad51 polymerization initiation. The threshold in ref.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed that the polymerization of hRad51 on dsDNA requires a minimal concentration of approximately 100 nM to initiate. This is consistent with previous results independently obtained both with conventional MT (20) and in single-molecule videomicroscopy (21) confirming the existence of a threshold concentration for hRad51 polymerization initiation. The threshold in ref.…”
Section: Discussionsupporting
confidence: 93%
“…In additions, the flow used in ref. 21 to keep molecules extended involves a stretching, which is nonuniform but can be high enough, especially at some places, to significantly increase hRad51 binding rate. Besides this minor discrepancy, data in refs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is highly dependent on the tension in the dsDNA template: disassembly stalls completely at forces above 50 pN. In addition, although the NPF can readily form in the presence of both ATP (van Mameren et al , 2009b) and ADP (Hilario et al , 2009), hRAD51 disassembly from dsDNA is critically dependent on ATP hydrolysis (van Mameren et al , 2009b). X‐ray crystallography has identified the location of the ATP‐binding pocket between adjacent monomers in the NPF (Conway et al , 2004).…”
Section: Introductionmentioning
confidence: 99%